Experimental determination of dynamic system simulation parameters for a bearingless rotating-field axial-force/torque motor. (May 2017) - Bauer, Walter; Freudenthaler, Paul; Gruber, Wolfgang; Amrhein, Wolfgang
The dynamic system simulation and the control design process of the new developed bearingless rotating-field axial-force/torque motor (AFTM) requires an augmented state-space framework for mathematical system description. After a short summary of this framework, the main focus of this paper concentrates on the model parameterization using state-of-the-art drive gauging procedures. A direct comparison features minor deviations between magnetostatic finite element analysis simulation results and available measurement data. Moreover, a closed-loop control concept for concurrent axial position stabilization and vector drive control of AFTMs is proposed. The quality of the closed-loop control system simulation is reviewed using relevant measurements of the functional prototype. A presentation of the disassembled prototype and a summary of its performance data concludes this paper.